Extensively hydrolyzed casein formula alone or with L. rhamnosus GG reduces β‐lactoglobulin sensitization in mice. Issue 3 (24th January 2017) - Aitoro, Rosita; Simeoli, Raffaele; Amoroso, Antonio; Paparo, Lorella; Nocerino, Rita; Pirozzi, Claudio; di Costanzo, Margherita; Meli, Rosaria; De Caro, Carmen; Picariello, Gianluca; Mamone, Gianfranco; Calignano, Antonio; et al.
Abstract: Background: Extensively hydrolyzed casein formula (EHCF) has been proposed for the prevention and is commonly used for the treatment of cow's milk allergy (CMA). The addition of the probiotic Lactobacillus rhamnosus GG (LGG) to EHCF may induce faster acquisition of tolerance to cow's milk. The mechanisms underlying this effect are largely unexplored. We investigated the effects of EHCF alone or in combination with LGG on β‐lactoglobulin (BLG) sensitization in mice. Methods: Three‐week‐old C3H/HeOuJ mice were sensitized by oral administration of BLG using cholera toxin as adjuvant at weekly intervals for 5 weeks (sensitization period). Two experimental phases were conducted: (i) EHCF or EHCF+LGG given daily, starting 2 weeks before the sensitization period and then given daily for 5 weeks and (ii) EHCF or EHCF+LGG given daily for 4 weeks, starting 1 week after the sensitization period. Diet free of cow's milk protein was used as control. Acute allergic skin response, anaphylactic symptom score, body temperature, intestinal permeability, anti‐BLG serum IgE, and interleukin (IL)‐4, IL‐5, IL‐10, IL‐13, IFN‐γ mRNA expression were analyzed. Peptide fractions of EHCF were characterized by reversed‐phase (RP)‐HPLC, MALDI‐TOF mass spectrometry, and nano‐HPLC/ESI‐MS/MS. Results: Extensively hydrolyzed casein formula administration before or after BLG‐induced sensitization significantly reduced acute allergic skin reaction, anaphylactic symptom score, body temperature decrease, intestinal permeability increase, IL‐4, IL‐5, IL‐13, and anti‐BLG IgE production. EHCF increased expression of IFN‐γ and IL‐10. Many of these effects were significantly enhanced by LGG supplementation. The peptide panels were similar between the two study formulas and contained sequences that could have immunoregulatory activities. Conclusions: The data support dietary intervention with EHCF for CMA prevention and treatment through a favorable immunomodulatory action. The observed effects are significantly enhanced by LGG supplementation.